The Capital Assets, Management, Earning, Liquidity - Wahyu Murti (Fakultas Ekonomi Universitas Borobudur, 2017)
Simultaneously Non Performing Loan ( NPL ) and Net Profit Margin significantly influence the Capital ,Assets,Management,Earning,Liquidity (CAMEL) with the acquisition ( R - square = 0.7682 ) . This condition is also able to explain the NPL and NPM , simultaneously contributing to the CAMEL in this case can be explained by the effect of 76,82 % , and the rest or 24,18% is as explaned residual estimation is influenced by other variables outside the model . Partially NPL has significan positive impact on CAMEL with the acquisition ( R - square = 0.7486) . This condition is also able to explain theNPL partially contributed to the CAMEL with the effect of 74,86 % Partially NPM has significan positive effect on CAMEL , it is shown by the acquisition ( R - square = 0.7372 ) . This condition is also able to explain , that the NPM partially contributed to the CAMEL ) with the effect by 73,72 % . Key words : Non Performing Loan ( NPL ), Net Profit Margin, the Capital Assets, Management, Earning, Liquidity (CAMEL)